2005
DOI: 10.1002/ajh.20382
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide–dexamethasone as primary therapy for advanced multiple myeloma

Abstract: The value of thalidomide-dexamethasone was assessed in 26 consecutive, previously untreated patients with multiple myeloma of high tumor mass. All showed Hgb < 8.5 g/dL, serum calcium > 11.5 mg/dL, or both. The response rate was 73%, frequency of early death < 3 months was 5%, projected median survival was 30 months, and projected median remission time was 25 months. There were no occurrences of grade 3 or 4 neutropenia or thrombocytopenia, so that serious infection occurred in only 12% of patients. Thalidomid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…46 Thal/dex did seem to induce a higher overall and CR rate, but more patients suffered progressive disease, indicating additional follow-up will be needed to determine which regimen provides a superior long-term outcome. Of note, however, two more mature single-arm studies of thal/dex have reported a briefer median time to progression and OS 47,48 than has been seen Abbreviations: MP, melphalan and prednisone; MPT, melphalan and prednisone with thalidomide; n, number of patients in each cohort Abbreviations: Mel 100, patients received two cycles of infusional vincristine, doxorubicin, and oral dexamethasone, followed by stem cell mobilization and up to two autologous stem cell transplants with melphalan as a preparative regimen at 100 mg/m 2 ; mos., months; MP, melphalan and prednisone; MPT, melphalan and prednisone with thalidomide; n, number of patients in each cohort with MPT, suggesting that thal/dex alone may not be optimal for nontransplant patients. Of greater interest may be the combination of thalidomide, pegylated liposomal doxorubicin, and dexamethasone (ThaDD ; Table 6), which was studied in 50 patients over the age of 65.…”
Section: Regimens Not Based On Mpmentioning
confidence: 99%
“…46 Thal/dex did seem to induce a higher overall and CR rate, but more patients suffered progressive disease, indicating additional follow-up will be needed to determine which regimen provides a superior long-term outcome. Of note, however, two more mature single-arm studies of thal/dex have reported a briefer median time to progression and OS 47,48 than has been seen Abbreviations: MP, melphalan and prednisone; MPT, melphalan and prednisone with thalidomide; n, number of patients in each cohort Abbreviations: Mel 100, patients received two cycles of infusional vincristine, doxorubicin, and oral dexamethasone, followed by stem cell mobilization and up to two autologous stem cell transplants with melphalan as a preparative regimen at 100 mg/m 2 ; mos., months; MP, melphalan and prednisone; MPT, melphalan and prednisone with thalidomide; n, number of patients in each cohort with MPT, suggesting that thal/dex alone may not be optimal for nontransplant patients. Of greater interest may be the combination of thalidomide, pegylated liposomal doxorubicin, and dexamethasone (ThaDD ; Table 6), which was studied in 50 patients over the age of 65.…”
Section: Regimens Not Based On Mpmentioning
confidence: 99%
“…As thalidomide and its analogs are more effective with earlier treatment initiation, they have been included in a variety of induction schedules with substantially lower thalidomide doses (100-200 mg/day), thereby minimizing toxicity [40][41][42]. It is possible that this dose may be able to be lowered even further in newer combination strategies [40][41][42][43][44]. The OPTIMUM study compared the tolerability and efficacy of high-dose dexamethasone (Dex) vesus 100, 200, or 400 mg of thalidomide for up to 12 cycles in 499 patients with relapsed/refractory MM, and demonstrated an improved time to progression (TTP) and response duration with all three thalidomide doses when compared to high-dose dexamethasone [45,46].…”
Section: Thalidomide and Thalidomide Analogsmentioning
confidence: 99%
“…As thalidomide and its analogs are more effective with earlier treatment initiation, they have been included in a variety of induction schedules with substantially lower thalidomide doses (100-200 mg/day), thereby minimizing toxicity [40][41][42]. It is possible that this dose may be able to be lowered even further in newer combination strategies [40][41][42][43][44].…”
Section: Thalidomide and Thalidomide Analogsmentioning
confidence: 99%
“…In the treatment of multiple myeloma, TH is increased up to 1,000 mg daily in combination with dexamethasone [65], whereas the same dose as monotherapy was not tolerated in patients with myelodysplastic syndrome [66]. Srinivas and Guardino [67] compared 200- with 800-mg doses of TH in patients with metastatic renal cell carcinoma and found advantages in tolerability and even survival for the lower dosage.…”
Section: Discussionmentioning
confidence: 99%